2015
DOI: 10.1016/j.neuroimage.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Brain dynamics in the comprehension of action-related language. A time-frequency analysis of mu rhythms

Abstract: a b s t r a c t a r t i c l e i n f oArticle history: Accepted 2 January 2015 Available online 9 January 2015 Keywords:Mu rhythms Beta rhythms Embodied meaning Action language Perceptive language EEG mu rhythms (8-13 Hz) recorded at fronto-central electrodes are generally considered as markers of motor cortical activity in humans, because they are modulated when participants perform an action, when they observe another's action or even when they imagine performing an action. In this study, we analyzed the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 84 publications
6
47
2
2
Order By: Relevance
“…The presentation of action related stimuli (both verbal and visual) induced significant power suppression in comparison to abstract language stimuli. In a second study by Moreno et al (2015), n o b-related (13-20 Hz) language effect could be observed, whereas l-power (6-13 Hz) got reduced during action sentence comprehension. However, the brange chosen in the second study differed from the range analyzed in the first study and comprised both b 1 -and b 2 -frequencies.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The presentation of action related stimuli (both verbal and visual) induced significant power suppression in comparison to abstract language stimuli. In a second study by Moreno et al (2015), n o b-related (13-20 Hz) language effect could be observed, whereas l-power (6-13 Hz) got reduced during action sentence comprehension. However, the brange chosen in the second study differed from the range analyzed in the first study and comprised both b 1 -and b 2 -frequencies.…”
Section: Introductionmentioning
confidence: 81%
“…Further, b-oscillations are very sensitive towards dissociation between concrete and abstract concepts (Weiss & Müller, 2013;Weiss & Rappelsberger, 1996. Recently, in the context of the embodied language theory, studies revealed that power decreases in the b-as well as the l-band are correlated with the processing of concrete action related language (Alemanno et al, 2012;Fargier et al, 2012;Moreno, de Vega, & León, 2013;Moreno et al, 2015;van Elk, van Schie, Zwaan, & Bekkering, 2010). This finding strongly sup-ports the theory of embodiment, which, in the case of language processing, indicates that understanding linguistic input requires a mental neural simulation of respective sensorimotor information in somatosensory and motor areas (Barsalou, 1999(Barsalou, , 2008Gallese & Lakoff, 2005;Glenberg & Kaschak, 2003; for a review see also Buccino, Colagè, Gobbi, & Bonaccorso, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the modulation (suppression) of mu and beta rhythms was similar in response to action sentences and videos and wasn't present for abstract sentences. In a follow‐up study, Moreno et al () tested the extent to which motor areas are activated during the comprehension of abstract ( You will doubt the patient's argument , translated from Spanish), perceptual ( You will notice the bright day ), and action ( You will cut the strawberry cake ) language. They found larger mu suppression in sentences with action and perception verbs compared to abstract sentences.…”
Section: The Role Of Sensorimotor Network In Language Comprehensionmentioning
confidence: 99%
“…The results showed larger mu and beta desynchronization in animal contexts compared to human contexts, thus arguing for the latter proposal. Further evidence comes from studies by Moreno et al (2013) and Moreno et al (2015). Moreno et al (2013) compared mu and beta suppression in response to action sentences, abstract sentences, and action videos.…”
Section: The Role Of Sensorimotor Network S In Language Comprehensionmentioning
confidence: 99%
“…Using behavioral measures of motor activity (e.g., grip force and posture changes), listening to action‐related verbs in sentences induces motor activity (da Silva, Labrecque, Caromano, Higgins, & Frak, ; Shiller et al, ), and however, this may be modulated by semantic context (Aravena et al, ). Studies using fMRI, TMS, MEG, and the EEG mu rhythm have found activation of the motor system when adults process (hear or read) verbs or phrases about actions (Di Cesare, Errante, Marchi, & Cuccio, ; Egorova, Shtyrov, & Pulvermüller, ; Hauk, Johnsurde, & Pulvermüller, ; Moreno et al, ; Moreno, de Vega, & León, ) or while decoding degraded speech sounds (d'Ausilio, Bufalari, Salmas, & Fadiga, ). Indeed, there is evidence that the motor system is functionally linked to representing action‐related language (Vukovic, Feurra, Shpektor, Myachykov, & Shtyrov, ), and some studies have also found left‐hemisphere specificity for the action‐language link (e.g., Pulvermüller, Hauk, Nikulin, & Ilmoniemi, ).…”
Section: Mirroring and Communicationmentioning
confidence: 99%